Phase diagram of carbonyl sulfide: An analogy to carbon dioxide and carbon disulfide. (3rd April 2017) - Yoo, Choong-Shik; Duwal, Sakun; Kim, Minseob; Ohishi, Yasuo
Abstract: The application of pressure, internal or external, transforms molecular solids into nonmolecular extended network solids with diverse crystal structures and electronic properties, ranging from optically nonlinear CO2 –V to high T c superconducting CS2 -III. While these transformations can be understood in terms of pressure-induced electron delocalization, the governing mechanisms are complex and often result in unusual phase/chemical transformation diagrams with a large number of polymorphs, metastable phases, and path-dependent phase behaviors. This complexity, commonly shared in many molecular systems at high pressures, poses both theoretical and experimental challenges in understanding high-pressure behaviors of dense molecular solids, particularly in the transition regime where the long-range interactions become comparable or even greater than hydrogen bonding at collapsed interatomic distances. In this paper, we describe the phase diagram of OCS, highlighting (i) the significance of long-range dipolar interaction that leads to the transition from linear phase I ( R 3 m ) to bent phase II ( Cm ) at 11 GPa, (ii) the molecular-to-nonmolecular transformations to highly disordered one-dimensional (1D) polymer phase III (modeled Cm ) at 22 GPa and 3D network phase IV (modeled P 21 21 21 ) at ∼35–45 GPa that becomes a semiconductor at around 100 GPa, and (iii) the intermediate nature of extended OCS between the two end members of CO2 and CS2 — an important chemical concept for molecular alloys. These results are based on our present low temperature and previous ambient temperature data obtained from confocal micro-Raman spectroscopy, synchrotron X-ray diffraction, and four-probe electric conductivity measurements.